2022
DOI: 10.1108/bij-08-2021-0508
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organizational justice on employee performance in the Indian Public Sector Units: the role of organizational identification

Abstract: PurposePast studies have proved the effect of justice on performance. However, the findings across studies have been inconsistent and there remains a substantial unexplained variance between the constructs. Therefore, justice researchers urge for further exploration of the underlying mechanism of the relationship by introducing influencers. This study responds to such call of the researchers by testing the influence of organizational identification (OID) on the justice-performance relationship in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Abaker et al (2023) studied employee performance at two companies in the United Arab Emirates. Pattnaik & Tripathy (2023) Previous research regarding the effect of working time on employee performance was conducted by Osisioma et al (2015); Daniel & Santeli (2020); Shadare & Olaniyan (2021); Soeryanto & Soemadi (2023) found that flexibility or effectiveness of working time has a positive effect on employee performance, but this research did not examine the influence of compensation factors on employee performance. In contrast to research conducted by Igbokwe et al (2020); Immawati (2022) found that working time has a negative effect on employee performance, but this research also did not examine the influence of compensation factors on employee performance.…”
Section: Introductionmentioning
confidence: 94%
“…Abaker et al (2023) studied employee performance at two companies in the United Arab Emirates. Pattnaik & Tripathy (2023) Previous research regarding the effect of working time on employee performance was conducted by Osisioma et al (2015); Daniel & Santeli (2020); Shadare & Olaniyan (2021); Soeryanto & Soemadi (2023) found that flexibility or effectiveness of working time has a positive effect on employee performance, but this research did not examine the influence of compensation factors on employee performance. In contrast to research conducted by Igbokwe et al (2020); Immawati (2022) found that working time has a negative effect on employee performance, but this research also did not examine the influence of compensation factors on employee performance.…”
Section: Introductionmentioning
confidence: 94%